2016
DOI: 10.1002/cm.21286
|View full text |Cite
|
Sign up to set email alerts
|

Stability properties of neuronal microtubules

Abstract: Neurons are terminally differentiated cells that use their microtubule arrays not for cell division but rather as architectural elements required for the elaboration of elongated axons and dendrites. In addition to acting as compression-bearing struts that provide for the shape of the neuron, microtubules also act as directional railways for organelle transport. The stability properties of neuronal microtubules are commonly discussed in the biomedical literature as crucial to the development and maintenance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
245
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(262 citation statements)
references
References 137 publications
4
245
0
Order By: Relevance
“…Here, we provide evidence for a common tau-mediated toxic mechanism for all six isoforms involving impairment of microtubule-based anterograde transport (plus-end directed, kinesin-based). The role of axonal transport in maintaining neuron connectivity and survival is well established (Kevenaar and Hoogenraad, 2015,Maday, et al, 2014), and the importance of microtubule-based transport extends to both the somatodendritic compartment and glial cells (Baas, et al, 2016,Kreft, et al, 2009). Indeed, microtubule-based transport is widely involved in intracellular trafficking for several cellular components including trafficking of myelin components in oligodendrocytes (Carson, et al, 1997,Lyons, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we provide evidence for a common tau-mediated toxic mechanism for all six isoforms involving impairment of microtubule-based anterograde transport (plus-end directed, kinesin-based). The role of axonal transport in maintaining neuron connectivity and survival is well established (Kevenaar and Hoogenraad, 2015,Maday, et al, 2014), and the importance of microtubule-based transport extends to both the somatodendritic compartment and glial cells (Baas, et al, 2016,Kreft, et al, 2009). Indeed, microtubule-based transport is widely involved in intracellular trafficking for several cellular components including trafficking of myelin components in oligodendrocytes (Carson, et al, 1997,Lyons, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules are intrinsically polarized, with beta-tubulin being present at the plusend and alpha-tubulin at the minus-end [2]. The intrinsic polarity of microtubules is recognized by molecular motor proteins, and allows for directional transport of cargoes along the microtubule surface.…”
Section: Axonal Transport: a Specialized Form Of Intracellular Traffimentioning
confidence: 99%
“…Unlike axons, microtubules in vertebrate dendrites display a non-uniform (mixed) orientation. Accordingly, unidirectional motor proteins could, in principle, move cargoes away and towards the neuronal soma within this subcompartment [2].…”
Section: Axonal Transport: a Specialized Form Of Intracellular Traffimentioning
confidence: 99%
“…These data suggest a functional link between MT acetylation patterns and brain aging, evidencing how the regulation of MT stability is critical during normal neuronal aging and supporting the concept that its failure may be a reliable candidate in causing neurodegenerative processes. Indeed, during the last years, an increasing body of evidence indicated the potential role of defective regulation of MT stability in neurodegenerative disorders [18] and, in particular, in Parkinson's Disease (PD) [19,20].PD is the second most common neurodegenerative disorder caused by the death of the dopaminergic neurons in the Substantia nigra [21] whose anatomy, with an average arborisation of 4.6 meters in humans [22], makes them particularly dependant on axonal transport which, in turn, depends on MT integrity and whose failure has been associated to the early phases of PD [23]. Although the identity of the real culprit of the pathology is still debated, in the recent years it is becoming ever clearer that MT destabilization is an early event in experimental and human models of PD, and many of the studies reported below strongly suggest that it can be followed by the hyper-stabilization of MTs, which could lead to detrimental side effects.…”
mentioning
confidence: 99%
“…These data suggest a functional link between MT acetylation patterns and brain aging, evidencing how the regulation of MT stability is critical during normal neuronal aging and supporting the concept that its failure may be a reliable candidate in causing neurodegenerative processes. Indeed, during the last years, an increasing body of evidence indicated the potential role of defective regulation of MT stability in neurodegenerative disorders [18] and, in particular, in Parkinson's Disease (PD) [19,20].…”
mentioning
confidence: 99%